DEVELOPMENT OF PROJECT-BASED WORKSHEETS ON THE UTILIZATION OF RED DRAGON LEATHER (Hylocereus costaricensis) FOR NATURAL COLOR OF PERCA FABRIC - Yuni Hernawati; Sari Sari; Yulia Sukmawardani (Gunung Djati Conference Series, 2021)
This study aims to analyze the validation test results and describe project-based worksheet products' appearanceon the utilization of red dragon fruit peel (Hylocereus costaricensis) waste for natural dye patchwork. The researchmethod used is Design-Based Research (DBR). The stages of this DBR method use the ADDIE design, whichconsists of 1) Analysis, 2) Design, 3) Development, 4) Implementation, and 5) Evaluation. The instruments usedwere worksheets, worksheet grids, validation sheets, and validation questionnaires filled in by three validators.The validation test percentage in this study was 86%, with a value of 0.86 obtained. Thus it can be concluded,learning media using project-based worksheets is declared valid.